2014
DOI: 10.1097/mcg.0b013e3182a87e5f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Procedural Sequence in Same-day Consecutive Bidirectional Endoscopy Using Moderate Sedation

Abstract: There were no significant differences in the patient's discomfort and satisfaction, regardless of the procedural sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Similar to the findings of previous reports, the duration and rate of detection of pathological findings did not differ significantly between the groups . Furthermore, we also found that satisfaction of the endoscopist, anesthetist, and patient did not differ significantly between both groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to the findings of previous reports, the duration and rate of detection of pathological findings did not differ significantly between the groups . Furthermore, we also found that satisfaction of the endoscopist, anesthetist, and patient did not differ significantly between both groups.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Carter et al . in 2014 showed no significant difference in the discomfort and satisfaction of patients during BDE, regardless of the procedural sequence …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Three other studies, using moderate or deep sedation for BDE, showed that EGD followed by colonoscopy was superior in terms of better EGD tolerability and lower sedative dosages . However, a recent study with moderate sedation found that there was no difference in patient discomfort and satisfaction regarding the procedure sequence . Because carbon dioxide (CO 2 ) is absorbed across the intestines more rapidly than air, CO 2 insufflation has commonly been used in colonoscopies to decrease abdominal discomfort during and e after the procedure .…”
Section: Introductionmentioning
confidence: 99%